Neurobiology and Therapeutic Potential of Cyclooxygenase-2 (COX-2) Inhibitors for Inflammation in Neuropsychiatric Disorders - Sethi, Rickinder; Gómez-Coronado, Nieves; Walker, Adam J.; Robertson, Oliver D’Arcy; Agustini, Bruno; Berk, Michael; Dodd, Seetal (Frontiers in Psychiatry, 2019)
Neuropsychiatric disorders, such as depression, bipolar, schizophrenia, obsessive-compulsive disorder, and neuropsychiatric disorders such as autism spectrum disorder, are associated with significant illness burden. Accumulating evidence supports an association between neuropsychiatric illnesses and inflammatory processes. Consequently, potent anti-inflammatory agents, such as the cyclooxygenase-2 inhibitors, represent a novel avenue to prevention and treatment of neuropsychiatric illness. In this paper, we first review the role of inflammation in psychiatric pathophysiology including inflammatory cytokines’ influence on neurotransmitters, the hypothalamic-pituitary-adrenal axis, and microglial mechanisms. Then we discuss how cyclooxygenase-2 inhibitors influence these pathways with potential therapeutic benefit. A search was conducted in PubMed, Embase, PsychINFO, and trial registries, Clinicaltrials.gov and The Stanley Medical Research Institute. The results were presented as a narrative review format. Currently available outcomes for randomized controlled trials up to November 2017 are also reviewed. The evidence reviewed here suggests cyclooxygenase-2 inhibitors may indeed help to treat the symptoms of neuropsychiatric disorders; however, further studies are required to assess appropriate illness stage-related indication.